Hearing screening results of refugee preschool and school children - Diala Hussein; Samet Kılıç; Wala’ Sami Alaqrabawi; Şule Çekiç; Meral Didem Türkyılmaz; Gonca Sennaroğlu (The Egyptian Journal of Otolaryngology)
Abstract Background The prevalence of refugees in Turkey has increased since the onset of the Syrian conflict. Refugees, as a demographic group, confront a spectrum of health challenges attributable to variables including malnutrition, restricted access to medical services, and unmanaged chronic health conditions. This study aims to investigate the hearing screening results among Syrian children in Ankara to assess the need for additional measures to raise awareness and to identify factors that may affect the hearing health of this population. Methods A total of 438 Syrian children (n = 876 ears), with a mean age of 7.41 ± 2.71 years, who attended the International Association for Asylum and Solidarity With Refugees centers, were enrolled in the study. Each child underwent otoscopic examination, tympanometry, and pure-tone audiometry screening. Results Of the tested ears, 225 (25.6%) exhibited abnormal otoscopic findings, 181 (20.7%) had tympanometry types other than type A, and 30 (3.4%) did not pass the pure tone audiometry screening. Of the 276 completed case history forms, 133 individuals reported relevant medical histories. Among them, 78 (58.6%) were consanguineous offspring, 10 (7.5%) had a family history of hearing impairment, 51 (38.3%) were currently experiencing flu, 42 (31.6%) had a history of recurrent flu, and 22 (16.5%) experienced otalgia. Notably, blast exposure was reported in 5 individuals (3.7%), and 6 individuals (4.5%) had mothers with a history of pregnancy complications. Conclusion Refugees represent a demographic cohort susceptible to various risk factors associated with hearing impairment. However, the findings of this study indicate that refugee children residing in Ankara exhibit normal hearing screening results. This outcome may be ascribed to factors such as having access to healthcare services and heightened awareness within the community.